PEMANFAATAN MEDIA BERBASIS ICT UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PADA PESERTA DIDIK KELAS V - QIFTIYAH, MARATUL (Universitas Nahdlatul Ulama Pasuruan, 2024)
This research was conducted to improve learning outcomes through ICT-based learning media in Indonesian language subjects and capital letter writing material. This type of research is classroom action research using a classroom action research flow design. This research was carried out over two cycles. Each cycle consists of four stages, namely action planning, action implementation, observation, and reflection. The subjects of this research were 27 students in class V of SDN 1 Sumber Agung. Research sources were obtained from observations of educators' and students' activities through written tests on students' learning outcomes. The research results show that there is an increase. Pre-cycle was 37.04%, cycle one was 66.67%, and cycle two was 88.89%. From the results of implementation and research on learning outcomes, it can be determined that using ICT-based learning media can improve student learning outcomes in capital letter writing material in class V at SDN 1 Sumber Agung.